A Greener Approach for the Chemoselective Boc Protection of Amines Using Sulfonated Reduced Graphene Oxide as a Catalyst in Metal- and Solvent-Free Conditions - Mittal, Rupali; Mishra, Anupam; Awasthi, Satish K. (Synthesis, 2020)
Sulfonated reduced graphene oxide (SrGO) has displayed great potential as a solid acid catalyst due to its efficiency, cost-effectiveness, and reliability. In this study, SrGO was synthesized by the introduction of sulfonic acid-containing aryl radicals onto chemically reduced graphene oxide using ultrasonication. The SrGO catalyst was characterized by Fourier Transform Infrared (FTIR) spectroscopy, Raman spectroscopy, powder X-ray diffraction (PXRD), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and transmission electron microscopy (TEM). Further, SrGO was effectively utilized as a metal-free and reusable solid acid catalyst for the chemoselective N-t-Boc protection of various aromatic and aliphatic amines under solvent-free conditions. The N-t-Boc protection of amines was easily achieved under ambient conditions affording high yields (84–95%) in very short reaction times (5 min–2 h). The authenticity of the approach was confirmed by a crystal structure. The catalyst could be easily recovered and was reused up to seven consecutive catalytic cycles without any substantial loss in its activity.
Keywords: Boc protection; sulfonated reduced graphene oxide; solvent-free; metal-free; heterogeneous catalysis